Mathematical Literacy Skills of Elementary Teacher Education Students through "Mathematics in Life" Approach - Rahmawati, Ika (International Conference on Elementary Education, 2022)
Elementary Teacher Education students are prospective elementary school teachers who will later teach mathematics to elementary school students who are in fact realistic mathematics, so prospective teachers must also learn how its application in the mathematical concepts learned. Another demand faced by elementary school teachers and students, especially at this time is the habituation of Literacy in all aspects of content delivered in elementary schools. Mathematical literacy is needed by students in solving problems of daily life. The purposes of this study are as follows: (1) to find out how the process of implementing Mathematics in life; (2) to find out how the ability of mastering mathematics literacy and (3) to find out how students respond after attending Mathematics in life class. This study uses a qualitative approach, in which two sampling techniques are used namely convenience and snowball sampling. The conclusions of this research are: (1) The process of implementing Mathematics in runs with tremendous enthusiasm from the students; (2) The ability of mastering mathematics literacy after implementing the stages of mathematical literacy in solving everyday problems is said to be quite good; and (3) Students' responses after taking Mathematics in Life based on literacy show positive responses.